CONJOINT ANALYSIS PADA PRODUK DENGAN MEDIA INTERNET - Irawan Wingdes (STMIK PONTIANAK, 2012)
Abstracts: cell phone is not uncommon these days, since its first discovery in 30 years ago, today the development in cell phone technology well exceeds expectation. Indonesia is one of the largest market in the world, its cell phone penetration is predicted to be 19 percent a year this research uses literature search to find what attributes are important when consumer purchases a cell phone. After the attributes are set, traditional conjoint analysis is used to determine relative importance of each attribute, followed by cluster analysis and one way anova. Data is gathered using internet especially direct email to respondent. The result of this research stated that branding, price and special feature of a cell phone is the most considered attribute when consumers purchase a cell phone.Keywords: conjoint analysis, relative importance attribute, consumer behavior